Cardiac Markers of EIH Athletes in Ultramarathon - Kim, Y.-J.; Kim, C.-H.; Shin, K.-A.; Kim, A.-C.; Lee, Y.-H.; Goh, C.-W.; Oh, J.-K.; Nam, H.-S.; Park, Y. (International Journal of Sports Medicine, 2012)
This study aimed to investigate effects of a 100-km ultramarathon on cardiac markers of exercise-induced-hypertensive marathoners. 10 marathoners with exercise-induced hypertension and 10 normal marathoners participated in the study. Their blood samples were collected before starting, at 50 km, and after finishing the course (100 km). Creatinine kinase was more significantly increased in the exercise-induced-hypertensive group than in the normal group at 100 km (P<0.05). N-terminal pro-brain nutriuretic peptide was significantly increased in the exercise-induced-hypertensive group at 50 km and 100 km (P<0.05) which was significant being doubled compared to the normal group (P<0.05). Exercise-induced-hypertensive marathoners showed a significant triple-increase in C-Reactive protein at 100 km (P<0.05). In conclusion, although the exercise-induced-hypertensive runners did not have myocardial damage during the 100 km ultramarathon, they had higher myocardial stress and more damage in active muscles due to a bloodstream disability.
Keywords: systolic blood pressure; exercise-induced hypertension; CK; CK-MB; NT-proBNP; myocardial stress